Proline and Abscisic Acid Content in Droughted Corn Plant Inoculated with Azospirillum sp. and Arbuscular Mycorrhizae Fungi - NOVRI YOULA KANDOWANGKO; GIAT SURYATMANA; NENNY NURLAENY; ROBERT DJONGGI MARULI SIMANUNGKALIT (Bogor Agricultural University, Indonesia, 2009)
Plants that undergo drought stress perform a physiological response such as accumulation of proline in the leaves and increased content abscisic acid. A research was conducted to study proline and abscisic acid (ABA) content on drought-stressed corn plant with Azospirillum sp. and arbuscular mycorrhizae fungi (AMF) inoculated at inceptisol soil from Bogor, West Java. The experiments were carried out in a green house from June up to September 2003, using a factorial randomized block design. In pot experiments, two factors were assigned, i.e. inoculation with Azospirillum (0, 0.50, 1.00, 1.50 ml/pot) and inoculation with AMF Glomus manihotis (0, 12.50, 25.00, 37.50 g/pot). The plants were observed during tasseling up to seed filling periods. Results of experiments showed that the interaction between Azospirillum sp. and AMF was synergistically increased proline, however it decreased ABA. Key words: Azospirillum sp., Arbuscular Mycorrhizae fungi, Corn, drought, proline, abscisic acid (ABA)